1993
DOI: 10.1136/pgmj.69.813.566
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of chronic pelvic pain, with special reference to sexual abuse. A study of 164 women

Abstract: Summary: Patients with chronic pelvic pain attending a tertiary referral centre show certain social, developmental and psychological characteristics. Specifically, they appear to have fewer children and to report more paternal overprotection, and a trend towards low maternal care compared to normals. They also show more depression, free-floating anxiety and somatic anxiety than such populations. The levels are similar to those found in other outpatient populations presenting with migraine or irritable bowel sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 32 publications
1
15
0
2
Order By: Relevance
“…It should be noted, however, that many studies had inconclusive results because of the methodology or design adopted, and that the role played by emotional factors in the onset and maintenance of the condition remains largely unknown 8,20,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that many studies had inconclusive results because of the methodology or design adopted, and that the role played by emotional factors in the onset and maintenance of the condition remains largely unknown 8,20,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other forms of abuse need to be identified since there was a significantly greater incidence of childhood physical abuse in patients with CPP compared with patients with other pain or with controls. 32 Rapkin et al 19 reported that 39% of patients with CPP had been physically abused during childhood and in this study physical abuse was more common than sexual abuse in the majority of these cases. However, many studies have failed to adopt comparative groups of patients with pain of equivalent chronicity.…”
Section: Somatisation Disordersmentioning
confidence: 46%
“…There was no other contact with the gynaecologist, but patients did undergo investiga tion (at 1 or 2 appointments) between these times, and if severely affected by pain and worried, they could contact the clinic nurse by telephone. This group formed a part of a larger study of 164 consecu tive referrals whose demographic, gynaecological and psychological characteristics have been reported elsewhere [17].…”
Section: Methodsmentioning
confidence: 99%
“…This tested for a second time the patient's view of the initial gynaeco logical consultation and served as a measure of reproducibility of the patient questionnaire. As part of the research interview the HDHQ was administered together with other instruments as previously reported [17]. The extent of pain was assessed both at the research interview (tl) and after the follow-up consultation (t2) using visual analogue scales completed by the patient for the worst pain experi enced during the previous 4 weeks and for the usual level of pain during the previous 4 weeks.…”
Section: Methodsmentioning
confidence: 99%